Transient bifurcation induced rocket acceleration leading to a relativistic bulk medium induced by designed high-intensity lasers - Ryutaro Matsui; Yasuaki Kishimoto (Physical Review Research)
By exploring a different function of plasma regulated by nonlinear waves and their transient bifurcations, we propose a boosting scheme for an object consisting of pure solid hydrogen medium irradiated by spatiotemporally designed high-intensity lasers to nearly the speed of light. This is achieved by two processes. One is the slow process via the formation of the shocklike structure in the medium and subsequent adiabatic compression exceeding 20 times the solid density to a width narrower than the local Debye length. This results in the frozen-in dynamics of the plasma regulated by the parameter ρ_{e}/γ_{e} ([electron charge density]/[electron relativistic factor]), which tends to be spatially less sensitive through the cancellation between laser ponderomotive and relativistic nonlinearities in a highly nonlinear regime. The other is the fast process of the transient bifurcation of the shock to a soliton leading to an explosion, which splits the structure into two shock structures propagating in opposite directions, i.e., one is boosted forward as the reaction of the other ejected backward as a fuel. The entire sequence of the processes causing compression and explosion, leading to the acceleration of bulk medium, are found to be highly stable and then robust without causing any serious instability even including the nonuniformity of laser intensity associated with a tight laser focal spot.